Multicentre, open-label, randomised, controlled clinical trial comparing 2% chlorhexidine–70% isopropanol and 5% povidone iodine–69% ethanol for skin antisepsis in reducing surgical-site infection after cardiac surgery: the CLEAN 2 study protocol. Issue 6 (17th June 2019) - Boisson, Matthieu; Corbi, Pierre; Kerforne, Thomas; Camilleri, Lionel; Debauchez, Mathieu; Demondion, Pierre; Eljezi, Vedat; Flecher, Erwan; Lepelletier, Didier; Leprince, Pascal; Nesseler, Nicolas; Nizou, Jacques Yves; et al.
Abstract : Introduction: Surgical-site infection (SSI) is the second most frequent cause of healthcare-associated infection worldwide and is associated with increased morbidity, mortality and healthcare costs. Cardiac surgery is clean surgery with low incidence of SSI, ranging from 2% to 5%, but with potentially severe consequences. Perioperative skin antisepsis with an alcohol-based antiseptic solution is recommended to prevent SSI, but the superiority of chlorhexidine (CHG)–alcohol over povidone iodine (PVI)–alcohol, the two most common alcohol-based antiseptic solutions used worldwide, is controversial. We aim to evaluate whether 2% CHG–70% isopropanol is more effective than 5% PVI–69% ethanol in reducing the incidence of reoperation after cardiac surgery. Methods and analysis: The CLEAN 2 study is a multicentre, open-label, randomised, controlled clinical trial of 4100 patients undergoing cardiac surgery. Patients will be randomised in 1:1 ratio to receive either 2% CHG–70% isopropanol or 5% PVI–69% ethanol for perioperative skin preparation. The primary endpoint is the proportion of patients undergoing any re-sternotomy between day 0 and day 90 after initial surgery and/or any reoperation on saphenous vein/radial artery surgical site between day 0 and day 30 after initial surgery. Data will be analysed on the intention-to-treat principle. Ethics and dissemination: This protocol has been approved by an independent ethics committee and will be carried out according to the principles of the Declaration of Helsinki and the Good Clinical Practice guidelines. The results of this study will be disseminated through presentation at scientific conferences and publication in peer-reviewed journals. Trial registration number: EudraCT 2017-005169-33 and NCT03560193.